Rancang Bangun Sistem Informasi Persediaan Obat Berbasis Web Menggunakan Model RAD - Biktra Rudianto; Yuni Eka Achyani; Indah Ariyati (JURNAL TEKNIK KOMPUTER AMIK BSI, 2021)
In this era of digitalization, there are many companies that have problems in delivering information. This makes the data management process slow, as well as providing information when needed, which hinders the process of selling or releasing goods. There are still many large companies in Indonesia that have not applied technology to be one of the reasons for the author to create a web-based inventory design application to facilitate the delivery of the required information, especially in information regarding reports of goods in and out, final stock reports and all problems related to stock. By designing the system towards a better direction, it is hoped that it can help and facilitate the ongoing system processes in managing data, including processing, compiling, and storing data which ultimately produces accurate data that can be used for company needs. The results of the analysis are described using the UML modeling language and applying the Rapid Application Development model. Implementation is in the form of the final result achieved, namely the formation of a web-based information system that can make it easier for users to process data.